2018
DOI: 10.1002/jts.22306
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Imagery Rehearsal Therapy and Cognitive Behavioral Therapy in Sexual Assault Victims With Posttraumatic Stress Disorder: A Randomized Controlled Trial

Abstract: Sleep disturbances are common among sexual assault victims with posttraumatic stress disorder (PTSD), but cognitive behavioral therapy (CBT) for PTSD does not directly address sleep-related symptoms. Trauma-related sleep disturbances are associated with more impairment and contribute to the maintenance of PTSD. In this study, we evaluated the efficacy of a combination of CBT and nightmare therapy (imagery rehearsal therapy; IRT) compared to CBT alone for the treatment of PTSD. We recruited 42 adult victims of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 41 publications
2
39
0
2
Order By: Relevance
“…However, these studies compared IRT to a waiting list control condition (Casement & Swanson, 2012 ; Yücel et al., 2020 ), whereas the current study compared add‐on IRT with an active control condition. The results of the current study are in line with two previous studies comparing IRT with an active psychotherapy control condition that reported a non‐significant change of sleep quality, nightmare frequency and PTSD symptoms (Belleville et al., 2018 ; Cook et al., 2010 ). The failure of the IRT treatment condition to reach superiority over the non‐IRT treatment condition in this study may thus partly be attributable to an effect of TAU, where elements of sleep‐enhancing treatment are part of the treatment sessions with the physician, psychologist and physiotherapist.…”
Section: Discussionsupporting
confidence: 92%
“…However, these studies compared IRT to a waiting list control condition (Casement & Swanson, 2012 ; Yücel et al., 2020 ), whereas the current study compared add‐on IRT with an active control condition. The results of the current study are in line with two previous studies comparing IRT with an active psychotherapy control condition that reported a non‐significant change of sleep quality, nightmare frequency and PTSD symptoms (Belleville et al., 2018 ; Cook et al., 2010 ). The failure of the IRT treatment condition to reach superiority over the non‐IRT treatment condition in this study may thus partly be attributable to an effect of TAU, where elements of sleep‐enhancing treatment are part of the treatment sessions with the physician, psychologist and physiotherapist.…”
Section: Discussionsupporting
confidence: 92%
“…The present study highlighted that age at time of abuse and number of perpetrators affect sleep disturbances in victims of sexual abuse. Where treatment of PTSD is concerned, the present results suggest that exploration of these characteristics could help clinicians to identify victims who could benefit from adding nightmares as a specific target for treatment (Belleville et al, 2018). Further work is needed to evaluate whether characteristics of sexual abuse correlate with treatment outcome.…”
Section: Discussionmentioning
confidence: 89%
“…This study analysed baseline data collected in the context of a larger trial of psychological treatment for PTSD (Belleville, Dube-Frenette, & Rousseau, 2018). The Laval University review board accepted the protocol, and each participant signed a consent form.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…In the absence of a significant additive effect on PTSD symptoms, an augmentation approach may nevertheless have meaningful impacts on engagement, response, and retention. Alternatively, while some augmentation approaches are no more effective at reducing global measures of PTSD symptoms, they may lead to improvements in the target of the augmentation specifically, which correspond to comorbid difficulties with PTSD (e.g., attentional bias, sleep impairments, cognitive functioning; see Beidel, Frueh, Uhde, Wong, & Mentrikoski, ; Belleville, Dubé‐Frenette, & Rousseau, ; Galovski et al, ), and are a treatment priority for patients.…”
Section: Resultsmentioning
confidence: 99%